2017
DOI: 10.4331/wjbc.v8.i1.81
|View full text |Cite
|
Sign up to set email alerts
|

Use of thyroglobulin as a tumour marker

Abstract: It is worthwhile to measure serum thyroglobulin (TG) level in thyroid cancer before subjecting patients to surgery for two reasons. Firstly, if the level is high, it may give a clue to the local and metastatic tumour burden at presentation; secondly, if the level is normal, it identifies the patients who are unlikely to show rising TG levels in the presence of thyroid cancer. Those who have high serum TG before surgery will show up recurrence as rising serum TG during the postoperative period. Those who do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Several studies found an inverse association between iodine intake and serum Tg (8,9). Moreover, there is an association between thyroid volume and serum Tg (10), and the levels of serum Tg significantly change with thyroid abnormalities and dysfunction such as thyroiditis, autoimmune thyroiditis, and thyroid cancer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found an inverse association between iodine intake and serum Tg (8,9). Moreover, there is an association between thyroid volume and serum Tg (10), and the levels of serum Tg significantly change with thyroid abnormalities and dysfunction such as thyroiditis, autoimmune thyroiditis, and thyroid cancer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the presence of TgAb may interfere with the measurement of Tg during the detection process, resulting in erroneous results. 16 Although thyroglobulin does not distinguish thyroid cancer from normal thyroid tissue, some studies 17 , 18 have shown that preoperative detection of thyroglobulin may help predict the tumor burden and lymph node metastasis of patients. A study in South Korea 19 believes that patients with preoperative thyroid globulin above 13.15ng/mL can be considered to have ipsilateral cervical lymph node metastasis, while above 30.05ng/mL may also have contralateral cervical lymph node metastasis, if higher than 62.9 ng/mL is at risk for distant metastases.…”
Section: Blood Markersmentioning
confidence: 99%
“…The midline uptake on RxWBS indicated the presence of large amounts of the remnant thyroid tissue postoperatively [24]. Regardless of the underlying pathology being benign or malignant, the serum Tg level could be increased because of the thyroid tissue burden [25]. In a previous report, Tg was higher in patients with midline uptake than in patients without it [11].…”
Section: Discussionmentioning
confidence: 86%